(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
By means of the decision of 26th February 2020, the German Federal Constitutional Court ruled § 217.1 StGB to be unconstitutional, in that it prevents the individual to decide in autonomy when and how to terminate life. This right stems from the conception of the man as a moral being capable of self-determination and self-responsibility, which is deeply rooted in the principle of human dignity (art. 1.1 GG). In this article I analyze the BVerfG’s decision and then I compare it with the Constitutional Court’s decision on the “Cappato case”, trying to discuss which solution would be best suitable for Italy.